2023
DOI: 10.1186/s12891-023-06821-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fibromyalgia syndrome in Saudi Arabia: a systematic review and meta-analysis

Yasser Bawazir

Abstract: Background The current systematic review and meta-analysis was conducted to estimate the prevalence of fibromyalgia syndrome (FMS) in Saudi Arabia. Methods A PRISMA systematic search appraisal and meta-analysis were conducted. A systematic literature search of English publications in PubMed, Embase, PsycINFO, Web of Science, MEDLINE, and Google Scholar, was conducted up to December 2022. Generic, methodological and statistical data was extracted fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…3 A systematic review found that FM affects 13.4% of the Saudi population. 4 Due to the debilitating nature of FM, it can significantly impair patients' quality of life and work productivity, 5,6 and it imposes a considerable economic, personal, and social burden. [7][8][9] In daily clinical practice, continuous assessment of the impact and severity of FM on patients is crucial for evaluating patients' status and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…3 A systematic review found that FM affects 13.4% of the Saudi population. 4 Due to the debilitating nature of FM, it can significantly impair patients' quality of life and work productivity, 5,6 and it imposes a considerable economic, personal, and social burden. [7][8][9] In daily clinical practice, continuous assessment of the impact and severity of FM on patients is crucial for evaluating patients' status and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia is a common reason for referral to a rheumatologist [ 1 ] and is estimated to affect from around 1 in 50 to 1 in 20 people, depending on the criteria used for classification [ 2 ]. Estimates of population prevalence are highly variable; for example, the population prevalence of fibromyalgia in the UK was estimated to be around 5.4% in 2015 [ 2 ] but, depending on the classification criteria, it can be considerably higher in other countries, for example, in Saudi Arabia, where it has been estimated to be 13.4% [ 3 ]. It is a pain state of no clear pathophysiological mechanism, with symptoms usually beginning in adolescence/early adulthood, although they can start later in life as well, and manifest as pain throughout the body, fatigue and cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%